2014
DOI: 10.1152/ajplung.00063.2014
|View full text |Cite
|
Sign up to set email alerts
|

Nox2-dependent glutathionylation of endothelial NOS leads to uncoupled superoxide production and endothelial barrier dysfunction in acute lung injury

Abstract: Microvascular barrier integrity is dependent on bioavailable nitric oxide (NO) produced locally by endothelial NO synthase (eNOS). Under conditions of limited substrate or cofactor availability or by enzymatic modification, eNOS may become uncoupled, producing superoxide in lieu of NO. This study was designed to investigate how eNOS-dependent superoxide production contributes to endothelial barrier dysfunction in inflammatory lung injury and its regulation. C57BL/6J mice were challenged with intratracheal LPS.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
30
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 58 publications
0
30
0
Order By: Relevance
“…A role for NOX2 in this particular posttranslational modification has recently been reported [98]. NOX2-specific inhibition prevents lipopolysaccharideinduced eNOS S-glutathionylation and reduces O 2 − production and permeability in lung microvascular endothelial cells.…”
Section: Interactions Indirectly Affecting Enos Functionmentioning
confidence: 94%
“…A role for NOX2 in this particular posttranslational modification has recently been reported [98]. NOX2-specific inhibition prevents lipopolysaccharideinduced eNOS S-glutathionylation and reduces O 2 − production and permeability in lung microvascular endothelial cells.…”
Section: Interactions Indirectly Affecting Enos Functionmentioning
confidence: 94%
“…Experimentally, increasing ROS by treatment with oxidants induces edema formation in isolated perfused lungs (6,52). Similarly, application of external oxidants or induction of intracellular ROS production worsens barrier function in vitro (5,40,67). Conversely, protective effects were reported with augmentation of endothelial antioxidant mechanisms (8,49,50).…”
mentioning
confidence: 99%
“…The role of eNOS in lung development, which may influence the clinical syndromes of neonatal respiratory distress, remains to be elucidated (Han et al, 2004). Wu et al (2014) suggested that eNOS uncoupling contributes to superoxide production and barrier dysfunction in the lung microvasculature after exposure to lipopolysaccharides. The results of this study also implicated the Nox2-mediated eNOS-S-glutathionylation in LPS-induced eNOS uncoupling in the lung microvasculature (Wu et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Wu et al (2014) suggested that eNOS uncoupling contributes to superoxide production and barrier dysfunction in the lung microvasculature after exposure to lipopolysaccharides. The results of this study also implicated the Nox2-mediated eNOS-S-glutathionylation in LPS-induced eNOS uncoupling in the lung microvasculature (Wu et al, 2014). A study of the SNP rs1799983 in NOS3 showed a significant increase in the GG genotype and G allele frequencies in groups with respiratory distress syndrome (Shen et al, 2014).…”
Section: Introductionmentioning
confidence: 99%